Educational consultancy in small states : a source book - Lloyd, Marie-Pierre (Commonwealth Secretariat LondonGB, 1994)
Focuses on the nature of and scope for consultancy. Describes the consultancy process in terms of its constituent phases and looks at the skills required for successful consulting. Examines some of the key considerations in running or developing consultancy as a business, and covers business planning, structure and administration, marketing and management of assignments.